Mogroside V Protects Porcine Oocytes From Lipopolysaccharide-Induced Meiotic Defects - Yan, Ke; Cui, Kexin; Nie, Junyu; Zhang, Hengye; Sui, Lumin; Zhang, Huiting; Yang, Xiaogan; Xu, Chang-Long; Liang, Xingwei (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence has demonstrated that lipopolysaccharide (LPS) compromises female reproduction, especially oocyte maturation and competence. However, methods to protect oocyte quality from LPS-induced deterioration remain largely unexplored. We previously found that mogroside V (MV) can promote oocyte maturation and embryonic development. However, whether MV can alleviate the adverse effects of LPS exposure on oocyte maturation is unclear. Thus, in this study, we used porcine oocytes as a model to explore the effects of MV administration on LPS-induced oocyte meiotic defects. Our findings show that supplementation with MV protected oocytes from the LPS-mediated reduction in the meiotic maturation rate and the subsequent blastocyst formation rate. In addition, MV alleviated the abnormalities in spindle formation and chromosome alignment, decrease in α-tubulin acetylation levels, the disruption of actin polymerization, and the reductions in mitochondrial contents and lipid droplet contents caused by LPS exposure. Meanwhile, LPS reduced m6A levels in oocytes, but MV restored these epigenetic modifications. Furthermore, MV reduced reactive oxygen species (ROS) levels and early apoptosis in oocytes exposed to LPS. In summary, our study demonstrates that MV can protect oocytes from LPS-induced meiotic defects in part by reducing oxidative stress and maintaining m6A levels.